Assessing the Practical Effectiveness of the Czech Republic’s AML System Using Statistical Evidence - Voina, Valeriu; de Batz de Trenquelléon, Laure Sabine Marie; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis evaluates the effectiveness of the anti-money laundering (AML) system in the Czech Republic. It focuses on how well different stages of enforcement, from suspicious transaction reports (STRs) through criminal complaints, prosecutions, and convictions, work together in practice. Based on official Czech statistics from recent years, the study begins with an outline of trends in the main indicators and then employs correlation analysis in testing consistency across enforcement stages, while also additionally for time lags. Along with statistical techniques, the thesis aims to explain major changes by referring to institutional and policy change. The results indicate that though the initial phases of the system are extremely active, there are significant weaknesses further along the chain, particularly in the transition towards successful convictions. A number of recommendations are posited based on the findings to enhance enforcement consistency and general effectiveness of the Czech AML system.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses